KAMPUNG KOTA SEBAGAI BAGIAN DARI PERMUKIMAN KOTA (Studi kasus Tipologi Permukiman RW 01 RT 02 Kelurahan Limba B dan RW 04 RT 04 Kel. Biawu Kecamatan Kota Selatan Kota Gorontalo) - Heryati . (Jurnal Inovasi, 2011)
Kampung is the part of urban settlement which source of all city problems in Indonesia, wheather from those slums area nor their crime either that always become from there. Government usually tried to rebuild the social life and the building condition of kampong, but couldn't solve a problem from kampong, especially social, economic and culture of the city. It's important to know the Typology of kampong in Gorontalo, which can develop them self as the good settlement toward as part of urban housing settlement.